Antibacterial activity of clays from Malaysian soils against food-borne Salmonella Typhimurium ATCC 14028 and Staphylococcus aureus ATCC 13565 - Azmi, Nur Naqiyah; Mahyudin, Nor Ainy; Wan Omar, Wan Hasyera; Mahmud Ab Rashid, Nor Khaizura; Ishak, Che Fauziah; Abdullah, Abdul Halim; Sharples, Gary J. (Multidisciplinary Digital Publishing Institute, 2021)
Natural clays have recently been proven to possess antibacterial properties. Effective natural antimicrobial agents are needed to combat bacterial contamination on food contact surfaces, which are increasingly more prevalent in the food chain. This study sought to determine the antibacterial activity of clays against the food-borne pathogens Salmonella typhimurium ATCC 14028 and Staphylococcus aureus ATCC 13565. Soils were processed to yield leachates and suspensions from untreated and treated clays. Soil particle size, pH, cation-exchange capacity, metal composition and mineralogy were characterized. Antibacterial screening was performed on six Malaysian soils via the disc diffusion method. In addition, a time-kill assay was conducted on selected antibacterial clays after 6 h of exposure. The screening revealed that Munchong and Carey clays significantly inhibit Salmonella typhimurium (11.00 ± 0.71 mm) and S. aureus (7.63 ± 0.48 mm), respectively. Treated Carey clay leachate and suspension completely kill Salmonella typhimurium, while S. aureus viability is reduced (2 to 3 log10). The untreated Carey and all Munchong clays proved ineffective as antibacterials. XRD analysis confirmed the presence of pyrite and magnetite. Treated Carey clays had a higher soluble metal content compared to Munchong; namely Al (92.63 ± 2.18 mg/L), Fe (65.69 ± 3.09 mg/L) and Mg (88.48 ± 2.29 mg/L). Our results suggest that metal ion toxicity is responsible for the antibacterial activity of these clays.